Lipomyelomeningocele for the urologist: Should we view it the same as myelomeningocele?. Issue 4 (August 2017) - Yerkes, E.B.; Halline, C.; Yoshiba, G.; Meyer, T.A.; Rosoklija, I.; Bowman, R.; McLone, D.; Cheng, E.Y.
Summary: Introduction: The primary urologic objectives for lipomyelomeningocele (LMM) and myelomeningocele (MM) are preserving renal integrity and achieving continence. Due to this common ground, LMM and MM are urologically treated the same. However, unlike MM, LMM may present with no evident functional concerns. Indications for and timing of tethered cord release (TCR) in LMM are therefore controversial. Long-term urologic outcomes are not well defined. Objective: Expectations for continence and potential for intermittent catheterization (CIC) following TCR in LMM are important for realistically counseling families regarding future needs. The present study aimed to identify prognostic factors for continence and need for CIC in LMM. Study design: The present study retrospectively identified 143 patients from the multidisciplinary clinic who underwent TCR for LMM between 1995 and 2010. Concomitant anorectal/genitourinary anomalies, filar lipoma, fatty filum, previous TCR, and follow-up <1 year were excluded. Analysis was limited to those toilet trained or aged ≥6 years at latest follow-up. Lipomyelomeningocele was classified as dorsal, distal, transitional or chaotic. Pre- and post-TCR urologic status was assessed. Ability to achieve urinary continence, with or without CIC, was the primary outcome, and need for CIC was the secondary outcome of interest. Results: A total of 56 patients met inclusion criteria. Median age at TCR was 4.4 months (range 1.0–224.0) with a median follow-up of 10.7 years (range 1.3–19.1); 68% were asymptomatic at presentation. Clinical symptoms were urologic in 7%. At the latest follow-up, 86% of patients were continent spontaneously or with CIC (Summary Fig.). Of the four patients who presented with urologic symptoms, all were continent, but three required CIC. Overall, 23% of patients required CIC. Median age at CIC initiation was 7.6 years (range 1.6–17.4). Long-term continence was not associated with any demographic, anatomic, surgical or functional variable. Need for CIC at latest follow-up was associated with symptomatic presentation, partial TCR, transitional lipoma, and high-risk pre-operative urodynamics. Discussion: In this series of primary TCR for LMM, where 93% of patients were urologically asymptomatic before TCR, prospects for continence were excellent. No studied parameter clearly impacted continence; however, need for CIC was associated with multiple variables. Conclusions: Clear predictors for continence after TCR will require additional long-term patient outcomes. Families can anticipate 23% likelihood of CIC, which is considerably less than in MM, but long-term urologic follow-up is still strongly recommended. Summary Figure Continence and CIC outcomes.